(untitled) (The Research of Medical Science Review, 2024)
Oligohydramnios with a reduced AFI and polyhydramnios with an increased AFI are associated with multiple perinatal risks in newborns, including IUGR, MAS, low Apgar scores, fetal death, and facial or skeletal abnormalities. Accordingly, the following research question has been developed for this current study: What are the common newborn complications in patients who have deranged AFI? An overall of 102 patients with singleton pregnancies with abnormal AFI after 4-quadrant ultrasound study were selected. Birth characteristics like early neonatal death, still birth, LGA, low apgar scores and NICU admission were noted. Consequently, the results showed that NICU admission was most frequent (37·2%), whereas low Apgar scores were 25·5%. The patients were aged 19 to 45 years with 29.37 ± 6.14 years, BMI of 18 to 29 kg/m² with 23.29 ± 2.58 and gestational age of 28 to 42 weeks with 38.47 ± 1.17. This study emphasizes the role of abnormal AFI volumes in fetal status recognition and aims at further investigation of this issue to decrease adverse neonatal results.